Physiological and biochemical alterations driven by light quality during germination and initial growth of the mandacaru cactus (Cereus jamacaru DC.) - Alves, Cleice Fátima G.; Daibes, L. Felipe [UNESP]; dos Santos Barbosa, Felipe; Moura, Flávia B. P.; Vieira Silva, José (Springer Nature, 2024)
Germination of many cacti across the Americas is light-dependent, but less has been explored regarding biochemical and morphophysiological alterations during germination and initial growth under different light spectra. Red and blue wavelengths, for instance, are predominantly absorbed by photosynthetic pigments, regulating plant growth. This study aimed to characterize physiological, anatomical and biochemical features of the mandacaru cactus (Cereus jamacaru DC.), an overexploited cactus crop from the Brazilian Caatinga, during germination and initial growth under white, red, and blue lights. Germination was tested under the three light treatments; the emerged seedlings were then cultivated under the same conditions. Seedling height and diameter were registered at 45, 60, 75, and 90 days after sowing. Photosynthetic pigments and total soluble sugars were quantified over time; anatomical analyses of the cladodes were also performed. White and red lights promoted the highest germination percentages (98–97%), with a decrease in the blue light (56%). Seedling height increased under the red light (35–36 mm) compared to the other treatments. Blue light tended to promote greater contents of chlorophylls and carotenoids. Total soluble sugars were greater in the blue light until 60 days, but equal among treatments at 75 and 90 days. Calcium oxalate crystals and amyloplasts were observed at 45 days in all treatments. This study shows contrasting physiological responses between light quality treatments, mostly related to the higher energy dissipation required under the blue wavelength. Future research should investigate seedling biomass production and relative growth rates, including comparisons with other populations of the mandacaru cactus.
Keywords: Cactaceae; Light-emitting diode; Photosynthetic pigments; Seedlings; Soluble sugars